PENGARUH KETERAMPILAN MENGAJAR GURU, FASILITAS BELAJAR, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA - Sulton Al Fikri, Moch; Masnawati, Eli; Masfufah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted based on the urgency of improving the quality of education in facing the challenges of human resource development towards the golden generation of 2045. Student learning outcomes are the main indicator of learning success that is influenced by various factors, including teacher skills in teaching, the availability of facilities, and student learning motivation. The purpose of this study is to analyze the influence of teacher teaching skills, learning facilities, and learning motivation on student learning outcomes at MTs Unggulan Al Jadid Waru Sidoarjo. This study uses a quantitative approach with a descriptive research type. The research sample amounted to 107 students selected through purposive sampling technique. Data collection was carried out through questionnaires and observations, with the questionnaire instrument using an eight-point Likert scale that has been tested for validity and reliability. Multiple linear regression tests, t-tests, simultaneous tests, and determination coefficient tests were used as the data analysis process. Student learning outcomes were proven to be significantly influenced by teacher teaching skills, learning facilities, and learning motivation, as shown in the research findings. In addition, student learning outcomes were proven to be significantly influenced by the three variables studied simultaneously.